Peranan Roh Kudus dalam Pertumbuhan Iman Orang Percaya dan Penerapannya dalam Kelas Pendidikan Agama Kristen - Ramses Simanjuntak (Sekolah Tinggi Theologia Nazarene Indonesia, 2015)
Today, most of believers are still relying on their strenght and taught to do thier daily activities. Sometimes, they are forget that they still need helps and God’s intervention. Before Jesus ascended into heaven, He promised that he would send the Holy Spirit to His disciples (Luke 24: 49). Not just that promise, He also promised that He would be with them until the end of the age (Mat. 28: 20). These passages show that God takes the roles in believers daily life.